Determination of climate risks in the construction industry against military actions - Goncharenko, Artem V. (Kyiv National University of Construction and Architecture, 2024)
The post-war reconstruction of Ukraine requires the introduction of low-carbon technologies in the construction sector and adaptation measures to climate change, taking into account greenhouse gas emissions caused by military actions in Ukraine. In this study, based on existing domestic and global regulatory documents on determining climate risks, chains of influence on climate risk are presented within the framework of assessing climatic factors that affect the calculated energy consumption data of a building at the project stage in the winter and summer periods. Preliminary calculations of the dynamics of changes in energy consumption for heating in the winter period for the city of Kyiv showed a decrease in energy consumption in two winter months by almost 16%, starting from 1942 for a conventional panel house with a wall area of 200 m2. While energy consumption for cooling in the hot period has been gradually increasing over the last decade. The forecast dynamics of the average monthly temperature according to the usual and wet bulb thermometer in July in 2050 is 26.371⁰С and 28.918⁰С, respectively. Modeling the dynamics of temperature increase for the city of Kyiv was carried out on the basis of climate databases: ECA&, Copernicus and the Central Geophysical Observatory named after B. Sreznevsky, as well as assessment reports on global climate change. The category of intermediate impacts included the impact of military actions on the urban environment and population, such as: an increase in the heat dome over the urbanized area, an increase in the heat index for public health, an increase in atmospheric air pollution. Possible adaptation measures should be taken depending on the specific reconstruction project throughout the life cycle of the facility, taking into account innovative low-carbon technologies, including the production of building materials. These studies may be promising in the future for finding ways to compensate for the mitigation of climate damage caused by Russia's military actions and neutralize this impact in modern buildings and structures.